Translation and validation of the drug avoidance self-efficacy scale for high-risk populations in Malaysia - Kamarudin, Engku Mardiah Engku; Alam, Nur Atiqah Puteri Mohd; Zainudin, Zaida Nor; Zakaria, Noor Syamilah; Kari, Dharatun Nissa Puad Mohd; Baharudin, Mohd Norbayusri (Scientific Research Publishing, 2024)
Self-efficacy plays a crucial role in treating individuals with addiction issues. It influences their willingness to seek treatment, follow therapeutic protocols, and bring about enduring behavioral changes. However, there is a lack of reliable psychometric instruments in the Malay language to gauge self-efficacy among Malaysians. This study aimed to translate and validate the Drug Avoidance Self-Efficacy Scale (DASES) into Malay, evaluate its reliability and internal con- sistency, and explore its content and construct validity among individuals with methamphetamine use disorders. The DASES assesses self-efficacy levels for abstaining from drug use in various high-risk situations. Translation, Content Validation Index (CVI), and calculation of Cronbach’s alpha coefficient were employed to assess the internal consistency of the final Malay version of DASES. The Malay translation of DASES tested among residents of Narcotics Addic- tion Rehabilitation Centers explained 70.39% of the total variance, which was adequate and had good Cronbach’s alpha values of 0.825. This study concluded that the Malay version of DASES is a valid and reliable tool for assessing self- efficacy levels in resisting drug use across diverse risk scenarios within Malay- speaking populations.